Analysis of Factors Causing Project Delay using Importance Index Method - Slamet Irwanto; Novika Candra Fertilia (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2021)
The government is build a new international airport in Majalengka, West Java. The concept of the West Java International Airport is the feel of a peacock on the roof of the terminal that makes the characteristics of grandeur, uniqueness, and good looking. During the construction of this project, there were various obstacles causing delays in the work. The purpose of this study is to determine the factors causing project delays and provide suggestions for managing the most influencing factors so that the causes of delays can be minimized so that the project can run according to a predetermined schedule. In this study the authors used quantitative research methods by distributing questionnaires to PT.BA employees as contractors who had been selected as competent respondents. This study uses 3 stages of questionnaire using validity and reliability tests using SPSS software version 25 and data analysis of importance index (IMPI). The results of this study are the West Java International Airport Terminal Roof Project has the 5 factors that most influence the work delays. including constraints on the procurement of imported materials (68.23%), delays in the delivery of material (67.24%), limited work access, due to other work related / lack of access (66.96%), improper construction methods causing errors during construction (64.92%) , and the application of new / specialized technologies that are not yet well known (62.30%).